Response of water and salt accumulation in vadose zone to groundwater level changes in coastal saline soils using HYDRUS-1D model - Feng Li; Shihong Yang; Yi Xu; Xiyun Jiao; Zewei Jiang (PLoS ONE, 2026)
Purpose Coastal saline soils are highly vulnerable to salinization, posing a major threat to sustainable agriculture. This study investigates how fluctuations in groundwater depth regulate water and salt dynamics in the vadose zone of a typical coastal saline area in Nanpi County, Hebei Province, China. The research focuses on quantifying changes in soil water storage and salt accumulation under different groundwater scenarios. Methods Field monitoring was combined with HYDRUS-1D simulations. Soil moisture and porewater salinity were measured using time-domain reflectometry and suction extractors, while laboratory analyses provided electrical conductivity and pH data. The HYDRUS-1D model was calibrated and applied to simulate three groundwater depth scenarios over a ten-year period. Results The model accurately captured water and salt transport in the vadose zone of the cotton field, with RMSE values below 0.05 for soil moisture and below 0.3 for soil salinity; model performance was better in deeper soil layers. Raising the groundwater level from 5.5 m to 3 m increased water storage by 45–47 cm in the upper 3 m of soil after ten years. Salt accumulation peaked near a depth of 450 cm and intensified near the surface under shallower groundwater, doubling the salinity in the top 60 cm and shifting the soil from mildly to moderately saline. Conclusions Groundwater depth critically affects soil water and salt redistribution in coastal saline environments. Shallow groundwater tables contribute significantly to topsoil salinization, highlighting the importance of managing groundwater levels within safe thresholds to support agricultural sustainability in susceptible regions.